STATUS REPRODUKSI DAN ESTIMASI OUTPUT SAPI PERANAKAN ONGOLE DI DESA PURWODADI DALAM DAN WONODADI, KECAMATAN TANJUNG SARI KABUPATEN LAMPUNG SELATAN - Sutrisno, Muhammad Adri; Sulastri, Sulastri; Siswanto, Siswanto; Suharyati, Sri (Jurnal Riset dan Inovasi Peternakan, 2018)
The aim of this research was to know the status of reproduction, NI, NRR, and Output  Grade Crossbred Ongole Cattle In Purwodadi Dalam Village And Wonodadi, Tanjung Sari District South Lampung Regency, Lampung Province. The research was carried out for two months, started in January until February 2018.  The data was taken from all of the cattle farmers Grade Crossbred Ongole Cattle in Purwodadi Dalam and Wonodadi Village. The result showed that reproduction status Grade Crossbred Ongole Cattle in Purwodadi Dalam is the first mating age of PO cattle was 17,62 months; S/C 1,80 months; calving interval 12,92 months; the age limit of female cattle maintenance 7,88 years; use of female cattle in breeding areas 6,47 years; natural increase 28,16 %; and output 28,64 % while reproduction status Grade Crossbred Ongole Cattle in Wonodadi Village is the first mating age of PO cattle was 17,89 months; S/C 1,98 months; calving interval 13,02 months; the age limit of female cattle maintenance 7,84 years; use of female cattle in breeding areas 6,17 years; natural increase 22,43 %; and output 23,06 %. Key words:  Status Reproduction, Estimation Output, Grade Crossbred Ongole Cattle